STRATEGI KEBIJAKAN UNIT KERJA REKAM MEDIS DENGAN METODE SWOT DI RS PHC SURABAYA - Kurnia Arofah; Efri Tri Ardianto; Dony Setiawan Hendyca Putra (Politeknik Negeri Jember, 2021)
Primasatya Husada Citra (PHC) Hospital Surabaya is one of the private hospitals that is required to providequality services one of which is a medical record. There are several points about medical records services thathave not been implemented optimally such as 43% incomplete filling of medical record files includingincomplete informed consent, and late return of medical record document by exceeded the standard 1x24hours. The purpose of this research is to determine the policy strategy in the medical record unit of the PHCHospital Surabaya using the SWOT method. The research method was the SWOT method that identifiedstrengths, weaknesses, opportunities, and threats. The research instruments used questionnaires andobservations. The subject of this research was 6 medical records officers. The results show that the value ofthe strength factor is 3.69 and the weakness factor is 1.42 while the opportunity factor value is 3.6 and thethreats factor is 1. The position of the medical record unit, PHC Hospital Surabaya, is in quadrant I so thesuitable strategy is SO (Strength-Opportunity), the strategy includes the development of integrated informationsystems, and improve the management of medical records related to recording and documentation formaintaining the quality of medical record documents.